The making of D-SAT: the development and testing of Dynamic Situation Awareness Task - Woller, Margo M. (Kansas State University, 2010)
Situation Awareness (SA) measurement takes on many forms: subjective, direct, and implicit performance, each with limitations. Subjective measures are based on self and peer reports, which allow biases to enter the measurement. Direct measures, such as SA Global Assessment Technique (SAGAT), interrupt SA in order to probe the participants’ SA level using questions. Implicit performance measures are based on participants’ ability to complete SA tasks, which must be created for each domain. A new approach, Dynamic – SA Task (D-SAT), was developed using a microworld wildfire fighting simulation, Networked Fire Chief (NFC). D-SAT is an implicit performance measure that can be adapted to multiple domains, for example inattentional blindness. Scenarios were developed during study one by tracking participant performance and scenario situations. Study two used the scenarios developed during study one to test D-SAT’s ability to evaluate SA by comparing D-SAT performance to an established SA performance measure, situation awareness global assessment technique (SAGAT). While the manipulation used to create had an effect on D-SAT performance, it was not associated with the established SA performance measure. However, a signal detection theory (SDT) analysis showed additional promise for D-SAT being a useful SA measure.
Keywords: Situation awareness; Signal detection theory; Dynamic situation awareness task; Situation awareness global assessment technique; Networked fire chief; Microworld simulation; Psychology, Cognitive (0633)